Oil palm waste as precursor of activated carbon for heavy metal removal - ZAINI, NUR FAZILAH BINTI; Othman, Norzila (Recent Trends in Civil Engineering and Built Environment, 2021)
Activated carbon is recognized as a potential adsorbent for many application due to its inexpensive cost, improved pores and excellent adsorption capabilities. At the moment, the growing availability of oil palm wastes is causing a slew of environmental issues. As a result, these agro wastes have the potential to be used as low-cost precursors for the manufacture of activated carbon. The generation of activated carbon from oil palm biomass is discussed in detail in this critical review. On the synthesis of activated carbons from oil palm biomass, the impacts of various process parameters on the pyrolysis stage, features, and effects of physical and chemical activating conditions are explored. This review is focus on removal heavy metal such arsenic, copper, aluminium and zinc. Heavy metal in wastewater from industrial activities will effected human, animal and plant. Throughout this research paper, strong emphasis is given to activated carbon made from oil palm waste will produce good activated carbon. This review paper was used Scopus to find prior study related to this study and extract the document to the software (VOSviewer) to get the visualization. Overall, this review article aids researchers in moving on with their investigations into a simple and cost-effective method for producing oil palm waste- based activated carbon with high physiochemical characteristics and adsorption capacity.